Simple Monetary Policymaking Without the Output Gap - Kai Leitemo; Ingunn Lønning (Norges Bank, 2002)
The performance of a simple monetary policy rule, which does not rely on explicit information about the output gap but instead uses the change in the rate of inflation as a proxy for the output gap, is explored in a simple model of the US economy. The rule is found to outperform an optimised Taylor rule under a reasonable specification of real-time output-gap uncertainty. The relative performance improves if the inflation process is more backward-looking, if demand or cost-push shocks are less prevalent, and if the output gap has a stronger effect on inflation.
hdl:11250/2498658
Keywords: E58; E52; E47; 330; Taylor rules; monetary policy; simple rules; uncertain output gap; inflation-only rule